ANALISIS LITERASI MATEMATIS SISWA MTs BERDASARKAN SOAL PISA : programme for international student assessment - Kafaha, Siti Aunillah (2017)
Penelitian ini dilatarbelakangi pentingnya mutu pendidikan di setiap jenjang pendidikan secara terencana, terarah dan berkesinambungan. Hasil tes PISA (Programme for International Student Assessment) telah menunjukkan bahwa kemampuan literasi matematis siswa masih rendah. Tujuan penelitian ini adalah: 1) mengetahui sejauh mana pencapaian literasi matematis siswa MTs berdasarkan soal PISA; 2) mengetahui sejauh mana pencapaian kemampuan literasi matematis siswa MTs klaster 2 dan klaster 3 berdasarkan komponen konten, konteks, dan proses; 3) mengetahui sejauh mana pencapaian kemampuan literasi matematis siswa MTs klaster 2 dan klaster 3 berdasarkan level penilaian PISA. Penelitian ini menggunakan penelitian model survey cross-sectional. Populasi dalam penelitian ini adalah seluruh siswa MTs dari klaster 2 dan klaster 3, dengan sampel sebanyak dua kelas yang mewakili masing-masing klaster. Instrumen yang digunakan dalam penelitian ini adalah soal-soal PISA. Kesimpulan penelitian ini adalah: 1) rata-rata pencapaian literasi matematis siswa adalah 34,4%; 2) persentase pencapaian literasi matematis siswa MTs klaster 2 lebih tinggi daripada klaster 3 berdasarkan komponen konten, konteks, dan proses pada penilaian PISA; 3) persentase pencapaian literasi matematis siswa MTs klaster 2 lebih tinggi daripada klaster 3 pada setiap level kecuali pada level 3.;---The study is motivated by the importance of the quality of education at every level of education in planned, directly, and continuously. The results of PISA tests (Programme of International Student Assessment) have shown that the ability of students' mathematical literacy is still low. The purpose of this study were: 1) to determine the extent to which the level of mathematical literacy ability of Islamic junior high school students based on PISA framework; 2) ) to determine the extent of mathematical literacy ability of Islamic junior high school students in second and third cluster based on PISA's component such as content, context, and process; 3) to determine the extent of mathematical literacy ability of Islamic junior high school students in second and third cluster based on the level of PISA's assessment. This study uses cross-sectional survey research model. The population in this study is all Islamic junior high school students from cluster 2 and cluster 3, with samples of two classes representing each cluster. The instruments used in this study are the questions of PISA. The conclusions of this study were: 1) the average of achievement of students' mathematical literacy is 34.4%; 2) the percentage of achievement of mathematical literacy of Islamic junior high school students in second cluster is higher than third cluster based on PISA's component such as content, context, and process; 3) the percentage of achievement of mathematical literacy of Islamic junior high school students in second cluster is higher than third cluster at each level except at third level.